Peculiarities of cellular compositions of peripheral blood and immune status of humans in Antarctic conditions - V. A. Stezhka; Ye. V. Moiseyenko; N. M. Dmytrukha; T. O. Bil'ko; O. M. Bakunovsky (Ukrainian Antarctic Journal, 2003)
Assessment of individual adaptation of 22 pretenders for long-term contract work in Antarctic in 2001-2002 and 11 winterers in early adaptation period (for 2 weeks) to new social-ecological environment in Akademik Vernadsky and after return from the station in a year was carried out.